2016
DOI: 10.1002/dmrr.2782
|View full text |Cite
|
Sign up to set email alerts
|

Activity and distribution of plasma platelet‐activating factor acetylhydrolase in women with gestational diabetes mellitus and their neonates

Abstract: The mothers with GDM presented with a state of chronic inflammation, and these mothers and their neonates also exhibited unfavourable metabolic profiles in terms of glucose and lipids. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…HDL‐associated Lp‐PLA2 is highly acknowledged to be anti‐inflammatory, while LDL‐associated Lp‐PLA2 is proinflammatory; however, the underlying mechanisms have yet to be elucidated. Alterations in the distribution of Lp‐PLA2 between LDL and HDL were detected in patients with various diseases, including atherosclerosis, dyslipidemias, DM, and PCOS . However, the clinical consequences of these alterations were inadequately determined .…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…HDL‐associated Lp‐PLA2 is highly acknowledged to be anti‐inflammatory, while LDL‐associated Lp‐PLA2 is proinflammatory; however, the underlying mechanisms have yet to be elucidated. Alterations in the distribution of Lp‐PLA2 between LDL and HDL were detected in patients with various diseases, including atherosclerosis, dyslipidemias, DM, and PCOS . However, the clinical consequences of these alterations were inadequately determined .…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Thus, controversy remains regarding whether plasma PAF-AH exerts a pro- or anti-inflammatory action. Given that H-PAF-AH, one of antioxidant enzymes of HDL, plays anti-inflammatory role [14, 19] and apoB-PAF-AH is associated with inflammation [13, 14, 24], it has recently been suggested that the relative distribution of the enzyme between apoB-containing lipoproteins and HDL determines its pro- or anti-inflammatory actions. Previous studies indicated that H-PAF-AH activity was decreased and the ratio of LDL-associated PAF-AH to H-PAF-AH activities and MDA levels were increased in women with PCOS, and the PAF-AH G994  →  T gene mutation is a risk factor for PCOS [19, 20, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma platelet-activating factor (PAF) acetylhydrolase (PAF-AH), also known as lipoprotein-associated phospholipase A2 (Lp-PLA2), is mainly bound to apolipoprotein (apo) B-containing lipoproteins, particularly low-density lipoprotein (LDL), and a small portion is also associated with high-density lipoprotein (HDL) [13, 14]. The abnormalities of plasma PAF-AH activity, mass and/or distribution in lipoproteins are associated with atherosclerosis and inflammatory diseases [1416].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pregnancies affected by GDM, maternal serum LpPLA 2 levels are elevated compared to healthy pregnant women 36 at time of delivery; no data on LpPLA 2 levels throughout gestation in GDM pregnancies exist. In GDM mothers, LpPLA 2 activity was associated with triglyceride levels, ApoB levels and LDL-C levels in multivariate regression analysis 36 .…”
Section: Introductionmentioning
confidence: 99%